2017
DOI: 10.1016/j.metabol.2017.01.019
|View full text |Cite
|
Sign up to set email alerts
|

First and second trimester gestational weight gains are most strongly associated with cord blood levels of hormones at delivery important for glycemic control and somatic growth

Abstract: Background Excessive gestational weight gain (GWG) during pregnancy is associated with adverse outcomes for mothers and offspring. Early, mid, and late pregnancy GWG have different associations with fetal growth and later life adiposity, but associations with cord blood hormones, which might predict later health, are not well studied. Methods In 978 pregnant women from the pre-birth Project Viva cohort, we calculated trimester-specific GWG using clinically recorded prenatal weights. Outcomes were levels of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
41
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 40 publications
3
41
1
1
Order By: Relevance
“…Neonates born to women with greater first‐trimester weight gain demonstrated higher mean cord blood levels of insulin (0.5 units per mL higher; 95% CI, 0.1‐0.9) and C‐peptide (0.06 ng/mL higher; 95% CI, 0.002‐0.009). Neonates born to women with higher second‐trimester weight gain demonstrated higher mean IGF‐1 (2.3 ng/mL; 95% CI, 0.6‐4.0), IGF‐2 (7.0 ng/mL; 95% CI, 1.2‐14.6), IGF binding protein‐3 (41.6 ng/mL; 95% CI, 19.4‐63.7), and leptin (0.9 ng/mL; 95% CI, 0.4‐1.4) . A Greek cohort studying 977 woman‐child pairs evaluated the association between trimester‐specific GWG and offspring fetal growth, obesity risk, and cardio‐metabolic health outcomes up to 4 years of age.…”
Section: Neonatal Outcomes Associated With Excessive Gestational Weigmentioning
confidence: 76%
See 1 more Smart Citation
“…Neonates born to women with greater first‐trimester weight gain demonstrated higher mean cord blood levels of insulin (0.5 units per mL higher; 95% CI, 0.1‐0.9) and C‐peptide (0.06 ng/mL higher; 95% CI, 0.002‐0.009). Neonates born to women with higher second‐trimester weight gain demonstrated higher mean IGF‐1 (2.3 ng/mL; 95% CI, 0.6‐4.0), IGF‐2 (7.0 ng/mL; 95% CI, 1.2‐14.6), IGF binding protein‐3 (41.6 ng/mL; 95% CI, 19.4‐63.7), and leptin (0.9 ng/mL; 95% CI, 0.4‐1.4) . A Greek cohort studying 977 woman‐child pairs evaluated the association between trimester‐specific GWG and offspring fetal growth, obesity risk, and cardio‐metabolic health outcomes up to 4 years of age.…”
Section: Neonatal Outcomes Associated With Excessive Gestational Weigmentioning
confidence: 76%
“…In utero programming may offer an explanation for these childhood outcomes. Rifas‐Shiman et al evaluated levels of adipokines, hormones that when dysregulated are implicated in obesity and weight gain, in umbilical cord blood samples . These hormones included insulin, C‐peptide (a marker of insulin), insulin‐like growth factor (IGF), and leptin.…”
Section: Neonatal Outcomes Associated With Excessive Gestational Weigmentioning
confidence: 98%
“…Weight gain in early pregnancy is primarily maternal fat gain and is associated with cord blood hormones related to offspring glucose and insulin regulation (during the 1 st trimester), while weight gain in later pregnancy is attributed to fetal, placental, and maternal gains and is associated with cord blood hormones related to offspring growth and adiposity (during the 2 nd trimester). 36 In general, findings from studies examining trimester-specific GWG rates suggest that mid-to-late pregnancy GWG rates are more strongly associated with infant anthropometric outcomes compared to early and later pregnancy. [6][7][8]13,16,17 Sridhar et al found that both 2 nd and 3 rd trimester GWG rates above the IOM recommendations were associated with LGA, while only inadequate 2 nd trimester GWG rates were associated with SGA.…”
Section: Discussionmentioning
confidence: 98%
“…Though GWG throughout pregnancy contributes to fetal growth and development, evidence suggests that timing of gains may differentially influence these outcomes. Weight gain in early pregnancy is primarily maternal fat gain and is associated with cord blood hormones related to offspring glucose and insulin regulation (during the 1 st trimester), while weight gain in later pregnancy is attributed to fetal, placental, and maternal gains and is associated with cord blood hormones related to offspring growth and adiposity (during the 2 nd trimester) . In general, findings from studies examining trimester‐specific GWG rates suggest that mid‐to‐late pregnancy GWG rates are more strongly associated with infant anthropometric outcomes compared to early and later pregnancy .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, first and second trimester GWG are directly associated with cord blood hormone levels (e.g., insulin, c-peptide, insulin-like growth factor-I (IGF-I) and IGF-II) at delivery. These growth-promoting hormones are vital for glycemic control and somatic growth and, when in excess, have been implicated in obesity predisposition and metabolic dysregulation [38]. On the other hand, a reduction in growthpromoting peptides has been noted in offspring cord blood of maternal exercisers [39].…”
mentioning
confidence: 99%